Analisis Kesadaran Mahasiswa dalam Menjaga Keamanan Data Pribadi pada Penggunaan Media - Muhammad Alief Rasyidin; Allyssa Putri; Maulina Diah Lestari; Riska Nurnajmah; Danish Alifian Safaraz (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the level of personal data security awareness among college students, an age group that is vulnerable to digital risks due to the intensity of social media use. The main objective of the research is to measure the extent to which students understand, behave, and behave in protecting their personal data in an ecosystem of digital platforms such as Instagram, Twitter, and TikTok. The research method used a descriptive quantitative approach through the distribution of questionnaires to 33 students. The results of the study show that students have a sufficient level of knowledge about the types of personal data and potential threats that may arise. However, it was found that there was a significant gap between knowledge and actual behavior, where most respondents were still negligent in activating security features and managing the privacy of social media accounts. These findings confirm that increasing awareness is not enough just through providing information, but must be followed by internalizing consistent data security attitudes and practices. Thus, this research makes an important contribution in understanding the pattern of student awareness of personal data security, as well as being the basis for the development of more effective digital education strategies to encourage safe behavior in cyberspace.